Structural deformation and displacement of a disc winding due to standard switching impulse voltage via finite element method - Md Yasid, Nurul Farahwahida; Azis, Norhafiz; Jasni, Jasronita; Mohd Yousof, Mohd Fairouz; Talib, Mohd Aizam; Murthy, Avinash Srikanta (Universiti Putra Malaysia Press, 2024)
Switching operations in a power system network can lead to transient overvoltage in the high voltage (HV) winding of distribution transformers that causes high-stress build-up. This paper presents the relationship between electromagnetic force due to a standard switching impulse (SSI) and mechanical deformation/displacement behaviours for a disc-type transformer. The analysis was carried out based on a three-dimensional (3D) modelling of a continuous HV disc winding configuration whereby it is subjected to the switching transient voltage and force excitations through the finite element method (FEM). The electric transient solver analysed the static and dynamic aspects of the electromagnetic forces associated with the variation of forces versus time. The transient structural solver evaluated the structural behaviours of the disc winding related to the axial height and radial width of the winding under electromagnetic forces. It is found that the positively dominant axial force generated in the winding with a magnitude of 8.7 N causes the top and bottom layers of disc winding to tilt and displace. In addition, the positive average radial force of 1.4 N causes the circumference of the winding to experience hoop tension and outwardly stretch. © Universiti Putra Malaysia Press.